2018
DOI: 10.1016/j.celrep.2018.04.025
|View full text |Cite
|
Sign up to set email alerts
|

RNA/DNA Hybrid Interactome Identifies DXH9 as a Molecular Player in Transcriptional Termination and R-Loop-Associated DNA Damage

Abstract: SummaryR-loops comprise an RNA/DNA hybrid and displaced single-stranded DNA. They play important biological roles and are implicated in pathology. Even so, proteins recognizing these structures are largely undefined. Using affinity purification with the S9.6 antibody coupled to mass spectrometry, we defined the RNA/DNA hybrid interactome in HeLa cells. This consists of known R-loop-associated factors SRSF1, FACT, and Top1, and yet uncharacterized interactors, including helicases, RNA processing, DNA repair, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

41
463
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 334 publications
(506 citation statements)
references
References 65 publications
41
463
1
1
Order By: Relevance
“…R-loops immunoprecipitated from HeLa cells with the S9.6 antibody (Cristini et al 2018). Although their study was performed using HeLa cells and our study was carried out with human B-cell extracts, 197 of the proteins identified in their study were also found in our study (Supplemental Table S1).…”
Section: Resultsmentioning
confidence: 56%
“…R-loops immunoprecipitated from HeLa cells with the S9.6 antibody (Cristini et al 2018). Although their study was performed using HeLa cells and our study was carried out with human B-cell extracts, 197 of the proteins identified in their study were also found in our study (Supplemental Table S1).…”
Section: Resultsmentioning
confidence: 56%
“…These data indicate that DDX5/DDX17 is required for transcription termination and transcript release steps of the human HSPA1A gene. We found that DHX9, which was implicated in transcription termination of β‐ and γ‐actin genes (Cristini et al, ), also copurified with hTHO (Supporting information Table S2). However, knockdown of DHX9 did not significantly alter the sizes of the HSP70 mRNA‐containing nuclear foci (Supporting information Figure S1b).…”
Section: Resultsmentioning
confidence: 86%
“…Aberrant R‐loops formed in the absence of THO interrupt DNA replication and induce genome instability (Gómez‐González et al, ; Santos‐Pereira & Aguilera, ). It has also been shown that various DNA and RNA helicases as well as XRN2 prevent the formation of transcriptional R‐loops (Boulé & Zakian, ; Cristini et al, ; Hodroj et al, ; Kim, Choe, & Seo, ; Morales et al, ). To test the possibility that aberrant R‐loop formation contributes to transcript accumulation of the human HSPA1A gene, we over‐expressed RNase H in THOC5‐ and DDX5/DDX17‐depleted cells, and HSP70 mRNA localization was analyzed by in situ hybridization.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations